2023
DOI: 10.1093/ijlct/ctad035
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nanoparticles on the evaporation of a salt water film

Abstract: The need for freshwater supply in different parts of the world has given great interest to the study of seawater desalination which has led to the development of various innovative techniques in this field. The present numerical study contributes to the improvement of the evaporative desalination operation by introducing nanoparticles into the base fluid. The desalination technique considered in this study consists of a saltwater film falling along the inner wall of a vertical channel heated uniformly by a con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…They also stated that the results would be more accurate if the salt concentration equation was computationally solved in the liquid phase. Nait Alla et al [23] used a finite difference method and parabolic governing equations to study the impacts of nanoparticles on the desalination process for a falling liquid film inside a vertical channel. They concluded that adding the nanoparticles into the liquid film increased the evaporation rate due to the change in thermophysical properties.…”
Section: Introductionmentioning
confidence: 99%
“…They also stated that the results would be more accurate if the salt concentration equation was computationally solved in the liquid phase. Nait Alla et al [23] used a finite difference method and parabolic governing equations to study the impacts of nanoparticles on the desalination process for a falling liquid film inside a vertical channel. They concluded that adding the nanoparticles into the liquid film increased the evaporation rate due to the change in thermophysical properties.…”
Section: Introductionmentioning
confidence: 99%